2020
DOI: 10.3390/v12111257
|View full text |Cite
|
Sign up to set email alerts
|

Monkeypox Virus in Nigeria: Infection Biology, Epidemiology, and Evolution

Abstract: Monkeypox is a zoonotic disease caused by monkeypox virus (MPXV), which is a member of orthopoxvirus genus. The reemergence of MPXV in 2017 (at Bayelsa state) after 39 years of no reported case in Nigeria, and the export of travelers’ monkeypox (MPX) from Nigeria to other parts of the world, in 2018 and 2019, respectively, have raised concern that MPXV may have emerged to occupy the ecological and immunological niche vacated by smallpox virus. This review X-rays the current state of knowledge pertaining the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
685
0
38

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 612 publications
(815 citation statements)
references
References 198 publications
(317 reference statements)
2
685
0
38
Order By: Relevance
“…The vaccinia-like virus infections were reported in different places and host species ( Dumbell and Richardson, 1993 ; Abrahão et al, 2015 ; Miranda et al, 2017 ), including humans ( Damaso et al, 2007 ; Megid et al, 2012 ). In different countries in Africa, human cases of MPXV infections have been reported ( Nakoune et al, 2017 ; Durski et al, 2018 ; Yinka-Ogunleye et al, 2019 ; Alakunle et al, 2020 ); imported MPXV cases were as well reported in Israel, the United Kingdom and Singapore ( Vaughan et al, 2018 ; Erez et al, 2019 ; Ng et al, 2019 ). In Europe, cases of cowpox were reported ( Tryland et al, 1998 ; Kalthoff et al, 2014 ; Ferrier et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The vaccinia-like virus infections were reported in different places and host species ( Dumbell and Richardson, 1993 ; Abrahão et al, 2015 ; Miranda et al, 2017 ), including humans ( Damaso et al, 2007 ; Megid et al, 2012 ). In different countries in Africa, human cases of MPXV infections have been reported ( Nakoune et al, 2017 ; Durski et al, 2018 ; Yinka-Ogunleye et al, 2019 ; Alakunle et al, 2020 ); imported MPXV cases were as well reported in Israel, the United Kingdom and Singapore ( Vaughan et al, 2018 ; Erez et al, 2019 ; Ng et al, 2019 ). In Europe, cases of cowpox were reported ( Tryland et al, 1998 ; Kalthoff et al, 2014 ; Ferrier et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Monkeypox virus is mainly transmitted to humans from wild animals such as rodents and primates, but transmission often occurs from humans to humans. Human to human transmission has been linked to respiratory droplets and contact with bodily fluids, a contaminated patient's environment or items, and a skin lesion on an infected individual (Alakunle et al 2020). Monkeypox virus has emerged as the most common orthopox virus after the eradication of the smallpox (Kantele et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Among Old World non-human primates, cynomolgus monkeys ( Macaca fascicularis ), sooty mangabeys ( Cercocebus atys ), orangutans ( Pongo pygmaeus ), and chimpanzees ( Pan troglodytes ) can be infected with MPXV. Among New World non-human primates [ 60 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ], the common marmosets ( Callithrix jacchus ) was shown to be susceptible to MPXV infection through intravenous inoculation [ 76 ] ( Table 1 ).…”
Section: Orthopoxvirusmentioning
confidence: 99%